Molecular epidemiology and genomic surveillance of human pegivirus: current insights and future directions - Dangana, Amos; Omoare, Adesuyi. A.; Miri, Nanpon; Samuel, Bwede E.; Dansura, Mangpin L.; Gagari, Villeng F.; Uzoebo, Nkiruka L.; Avong, James; Okoh, John; Jinadu, Olakitan; Demola, Onakomaiye; Babatunde, Olajumoke; et al. (International Journal Of Community Medicine And Public Health, 2026)
Human pegivirus (HPgV), formerly termed GB virus C (GBV-C), is a widely circulating, non-pathogenic RNA virus within the Flaviviridae family. Although highly prevalent globally, HPgV remains insufficiently characterized despite growing evidence of its immunomodulatory effects, particularly among individuals co-infected with HIV or HCV. Improved understanding of its genetic diversity, transmission patterns, and evolutionary dynamics is crucial to elucidate its potential biomedical relevance. The contemporary evidence on the molecular epidemiology and genomic surveillance of HPgV, emphasizing research gaps, geographic disparities, and priorities for future study. A systematic peer-reviewed literature and publicly available genomic repositories such as GenBank and GISAID was conducted for studies published between 1995 and 2025 using terms including “HPgV,” “GBV-C,” “molecular epidemiology,” “genomic surveillance,” and “genotype distribution.” Extracted data were classified by region, genotype, and study design to evaluate trends in prevalence, genetic variability, sequencing coverage, and the strength of surveillance systems. The review reveals substantial global genetic diversity, comprising at least seven recognized genotypes with distinct regional distributions. Despite diversity, HPgV remains underrepresented in genomic studies, particularly in low- and middle-income countries. Limitations include scarce full-genome sequencing, inconsistent genotype classification, and limited integration into global pathogen surveillance platforms. While co-infection with HIV and HCV poses analytical challenges, it also offers opportunities to investigate HPgV-associated immune modulation. Although clinically benign, HPgV’s widespread distribution and possible immunological influence highlight the need for enhanced genomic monitoring, standardized nomenclature, and expanded sequencing capacity. Coordinated global efforts are essential to strengthen HPgV surveillance and advance understanding of its evolutionary behavior and public health implications.